Clinical Relevance and Potential Applications of Brachial-Ankle Pulse Wave Velocity: Current Evidence and Future Perspectives - Hack-Lyoung Kim (Journal of Clinical Medicine, 2026)
Arterial stiffness is increasingly recognized as an important marker of vascular aging and an independent predictor of cardiovascular disease. Among the available methods for assessing arterial stiffness, brachial-ankle pulse wave velocity (baPWV) has gained widespread clinical acceptance because it is simple, noninvasive, highly reproducible, and suitable for routine practice and large-scale population screening. Accumulating evidence has demonstrated that baPWV is associated with hypertension-mediated target organ damage, coronary artery disease, cardiovascular events, and mortality. Beyond its prognostic value, baPWV has been investigated as a potential marker of vascular responses to pharmacological and lifestyle interventions. Emerging evidence also suggests that serial assessment and visit-to-visit variability of baPWV may provide additional prognostic information, although their clinical applicability requires further validation. Another advantage of baPWV is its simultaneous measurement of the ankle-brachial index, enabling comprehensive assessment of both arterial stiffness and peripheral artery disease without additional examination time. This review summarizes the physiological basis, measurement principles, strengths and limitations, and current clinical applications of baPWV, with particular emphasis on cardiovascular risk stratification, target organ damage, therapeutic monitoring, serial assessment, and combined ankle-brachial index evaluation. Finally, future perspectives for integrating baPWV into precision cardiovascular medicine are discussed.